Coutumes et religion : quelques hypothèses à partir des lois sur l’idolâtrie de la michna Avoda Zara et du De idololatria de Tertullien - Stéphanie É. Binder (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
Mishna Avoda Zara and Tertullian’s De idololatria offer Jews and Christians ways to manage their daily life without endangering their faith while surrounded by the culture infused with idolatry of the Roman Empire in which they live. Facing the reality of their followers’ behaviour, who have no intention to renounce certain traditions or activities critical for their daily survival, even though they contravene religious principles, the redactors of the texts are compelled to adapt themselves and to find a way to justify the persistence of some traditions in their endeavour to characterize a communitarian identity. This survey examines some of the mechanisms they use to do so.